What Global Emission Regulations Should Corporations Support? - Burress, David (Journal of business ethics, 2005)
In their role as political actors and lobbyists, corporations have responsibilities to help determine the existence and content of global regulations of pollutants. The ethical nature of those responsibilities is highly sensitive to the assumed normative framework. This paper compares several frameworks by modeling them as differently weighted versions of utilitarianism. Under a strict neoclassical approach, corporations have a narrow obligation to maximize profits, which generally entails opposing emission regulations. In contrast, a stakeholder approach as well as Marxian and common ethics approaches suggest that firms have an obligation to actively support sustainable emission regulations with the following properties , major restrictions would be global rather than local, global restrictions would apply in all cases of persistent emissions, global restrictions would apply to non-persistent emissions as well, unless they have been affirmatively shown to be safe using reasonably persuasive scientific evidence, safety thresholds would be set fairly restrictively, based on administrative models and rules of thumb, in light of existing scientific knowledge but without requiring full scientific justification, long-run goals would include zero emission of persistent unsafe substances., However, the stakeholder approach supports phase-in rules to mitigate short-run compliance costs.